Immune Checkpoint Inhibitors and Venous Thromboembolism: An Analysis of the WHO Pharmacovigilance Database. Issue 1 (2nd May 2022) - Allouchery, Marion; Beuvon, Clément; Pérault‐Pochat, Marie‐Christine; Roblot, Pascal; Puyade, Mathieu; Martin, Mickaël
Abstract : Data on venous thromboembolic events (VTEs) in patients receiving immune checkpoint inhibitors (ICIs) are scarce and conflicting. This study investigated the risk of reporting VTEs associated with ICIs in comparison with all other anticancer drugs. The World Health Organization pharmacovigilance database (VigiBase), comprising >30 million individual case safety reports, was queried. All reports on patients with cancer, involving at least one anticancer drug as a suspect or interacting drug and registered from January 1, 2008, to May 31, 2021, were included. The association between ICIs and the risk of reporting VTEs was estimated using the reporting odds ratio (ROR) as a measure of disproportionality with all other anticancer drugs as comparators. RORs were estimated as crude and adjusted RORs for age, sex, and other medications (excluding anticancer drugs) associated with risk of VTEs. Among 1, 196 patients experiencing VTEs after ICI treatment, the median age was 65 years and 57.6% were men. Anti‐PD‐1 agents (62.5%) were the most frequently reported. ICIs were not associated with higher reporting of VTEs when compared with other anticancer drugs (crude ROR 0.63, 95% confidence interval (CI) 0.60 to 0.67 and adjusted ROR 0.70, 95% CI 0.65–0.74). No signal of disproportionate reporting was found when considering each class of ICIs. In conclusion, ICIs were not associated with higher reporting of VTEs, in comparison with all other anticancer drugs in a large‐scale pharmacovigilance database. Owing to the limitations inherent to pharmacovigilance studies, prospective studies, including an adequate comparison group, are needed to assess the risk of VTEs in ICI‐treated patients.